2021
DOI: 10.1002/acp.3844
|View full text |Cite
|
Sign up to set email alerts
|

The usual suspects: How psychological motives and thinking styles predict the endorsement of well‐known and COVID‐19 conspiracy beliefs

Abstract: Summary Research on belief in conspiracy theories identified many predictors but often failed to investigate them together. In the present study, we tested how the most important predictors of beliefs in conspiracy theories explain endorsing COVID‐19 and non‐COVID‐19 conspiracy theories and conspiracy mentality. Apart from these three measures of conspiratorial thinking, participants ( N = 354) completed several measures of epistemic, existential, and social psychological moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 81 publications
2
34
0
5
Order By: Relevance
“…Such worldviews allow people to maintain their beliefs over time rather than experience the distress of confronting disconfirmatory evidence. In addition, CT beliefs can also be a way to justify certain behaviours or reject official narratives that are inconsistent with broader views about government and the role of the authorities (e.g., contest the existence of the COVID-19 virus), that confront rather complex topics (e.g., the diverse consequences of a complex health crisis, Douglas, 2021;Georgiou et al, 2020;Gligori c et al, 2021). Moreover, as Cichocka et al (2016) suggest, these CTs can allow a person to validate their beliefs and strengthen their sense of in-group membership and thereby allow them to impute blame for negative outcomes to external parties (e.g., governing bodies) or expert figures of power (e.g., Bill Gates's role in the COVID-19 pandemic response; Georgiou et al, 2020).…”
Section: Motivational Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such worldviews allow people to maintain their beliefs over time rather than experience the distress of confronting disconfirmatory evidence. In addition, CT beliefs can also be a way to justify certain behaviours or reject official narratives that are inconsistent with broader views about government and the role of the authorities (e.g., contest the existence of the COVID-19 virus), that confront rather complex topics (e.g., the diverse consequences of a complex health crisis, Douglas, 2021;Georgiou et al, 2020;Gligori c et al, 2021). Moreover, as Cichocka et al (2016) suggest, these CTs can allow a person to validate their beliefs and strengthen their sense of in-group membership and thereby allow them to impute blame for negative outcomes to external parties (e.g., governing bodies) or expert figures of power (e.g., Bill Gates's role in the COVID-19 pandemic response; Georgiou et al, 2020).…”
Section: Motivational Perspectivesmentioning
confidence: 99%
“…International opinion polls suggest that conspiracy theory (CT) beliefs are now more widely adopted, and circulated across western countries than ever, with recent events such as the COVID-19 protests and Capitol riots being strong outward manifestations of these belief systems (Depoux et al, 2020;Georgiou et al, 2020;Gligori c et al, 2021;O'Connell et al, 2021;Sallam, 2021;Uddin et al, 2021;YouGov-Cambridge Globalism Project, 2020). Although CTs offer sometimes intriguing narratives of events (e.g., the JFK assassination by multiple actors), they are usually false and can lead to unjustified mistrust of authorities, rejection of vaccinations and harmful or hurtful rejection of crimes against humanity (Douglas et al, 2015;Georgiou et al, 2020;Jolley & Douglas, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this case the intuitive answer is 'first place'; however, of course, if you pass the person in second place then you are in second place [16]. Most of the work using measures of analytic thinking has revealed a small to moderate relationship with conspiracy beliefs [6,9,[17][18][19][20][21][22][23][24][25][26][27][28][29], such that an increased reliance on intuitive thinking is associated with conspiracy beliefs, while analytical thought appears to protect against such beliefs (and some evidence indicates that conspiracy beliefs are more strongly associated with higher intuitive thinking than lower analytic thinking) [30].…”
Section: Dual-process Theorymentioning
confidence: 99%
“…Indeed, Romer and Jamieson ( 2021b ) found that the use of conservative media (e.g., Fox News) and social media (e.g., Facebook and Twitter) by U.S. residents was positively related to conspiracy beliefs related to the COVID-19 pandemic, whereas reliance on mainstream print (e.g., New York Times and Washington Post) predicted a decrease in such conspiracy beliefs. However, it should not be overlooked that individual characteristics, such as tendencies toward analytical thinking and spirituality (Gligorić et al, 2021 ), as well as the educational level (Georgiou et al, 2019 ), strongly interact with conspiracy beliefs, and thus measures taken by policymakers, academics, and the media can hardly lead to a reduction of conspiracy belief among all people.…”
Section: Discussionmentioning
confidence: 99%